APPLICATION OF NANOSTRUCTURES IN PHOTOVOLTAIC ENERGY SOURCES - Eshboltayev Iqbol Mamirjonovich,; G‘ofurov Saidkamol Zokirjon ogli,; Eshboltayev Ikromjon Iqbol ogli, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This  paper  discusses  the  application  of  nanostructures  and  nanomaterials  in photovoltaic (PV) energy sources, their main types, operating mechanisms, and their role in improving the efficiency of solar cells. New-generation solar cells developed based  on  nanotechnologies  enable  increased  energy  conversion  efficiency,  reduced material consumption, and the creation of flexible and low-cost energy sources.